Глобализация и постмодерное общество - Ильюшина, Э. (Социология: теория, методы, маркетинг, 2004)
Globalization has become very popular in many social sciences. The article deals with studies on essence of globalization as a social and economic process, and its influence on formation of the postmodern society in the West, where it is considered to be a model to follow suit. The author describes some characteristics of the western techno logically developed society related to globalization in order to question its attractiveness as a model for Ukrainian society developing its own national state.